2003
DOI: 10.1074/jbc.m210929200
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Thermal and Conformational Properties of the Rhodopsin Congenital Night Blindness Mutant Thr-94 → Ile

Abstract: Naturally occurring point mutations in the opsin gene cause the retinal diseases retinitis pigmentosa and congenital night blindness. Although these diseases involve similar mutations in very close locations in rhodopsin, their progression is very different, with retinitis pigmentosa being severe and causing retinal degeneration. We report on the expression and characterization of the recently found T94I mutation associated with congenital night blindness, in the second transmembrane helix or rhodopsin, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…Janz et al (51) In addition, congenital night blindness mutants that are characterized by an open conformation of the chromophorebinding site for nucleophiles have been identified. For example, T94I opsin folds properly and binds 11-cis-retinal to form pigment, but T94I Rho displays reduced thermal stability, has a long lived Meta II photostate, and shows highly increased reactivity toward NH 2 OH in the dark compared with WT Rho (54,55). In addition, it has been shown that T94I opsin is constitutively active (55).…”
Section: Discussionmentioning
confidence: 99%
“…Janz et al (51) In addition, congenital night blindness mutants that are characterized by an open conformation of the chromophorebinding site for nucleophiles have been identified. For example, T94I opsin folds properly and binds 11-cis-retinal to form pigment, but T94I Rho displays reduced thermal stability, has a long lived Meta II photostate, and shows highly increased reactivity toward NH 2 OH in the dark compared with WT Rho (54,55). In addition, it has been shown that T94I opsin is constitutively active (55).…”
Section: Discussionmentioning
confidence: 99%
“…The G90D mutant is associated with the retinal disease congenital night blindness, and the aspartate in the mutant would be in the retinal binding pocket next to the Schiff base (55). In the same region, another mutation related to congenital night blindness, T94I, is reported to have very unusual thermal and conformational properties (44). Gly-89 forms a cavity together with glycine 90, and a water molecule is located very close to the carbonyl group of Gly-89 at hydrogen-bonding distance (10).…”
Section: Discussionmentioning
confidence: 99%
“…The mutant proteins in the dark are less stable than WT, with the stability decreasing with increasing size of the side chain. A number of factors are shown to affect the thermal stability of dark-state rhodopsin, including retinal disease-causing mutations (44) or zinc binding (45). Other factors mediating the stability of dark-state rhodopsin are proposed, like a conserved ion-pair interaction in the intradiscal loop E-2 of rhodopsin (46).…”
Section: Discussionmentioning
confidence: 99%
“…We used this approach because retinal absorbance decreases after Schiff base hydrolysis (52), and this type of analysis is widely used to assess retinal-protein stability in purified rod and cone visual pigments (30,53,54).…”
Section: Xenopus Opn4xmentioning
confidence: 99%